The Effect of Good Agriculture Practices (GAP) on Soybean Productivity with Cobb-Douglas Production Function Analysis in Kulon Progo Regency - Fitry Purnamasari; Lestari Rahayu Waluyati; Masyhuri Masyhuri (Agro Ekonomi, 2017)
This study aims to determine the level of adoption of Good Agriculture Practices (GAP) and the influence of GAP and other factors of production on soybean productivity. The number of respondents in this research is 50 farmers taken randomly. This research used proportional parameter test and multiple linear regression analysis with Ordinary Least Square (OLS) method. This research has been declared valid, reliability, data have been the normal distribution, free from multicollinearity and heteroscedasticity problem. The result of the analysis shows that (1) the adoption rate of GAP of soybean farmers in Kulon Progo Regency is categorized as a high category. Farmers adopted 83,07% of the overall GAP portion of the input, land preparation, planting, fertilizing, crop protection, irrigation, harvesting, and post-harvest. (2) The result of the R2 test shows that 47,8% variation of soybean productivity can be explained by the eight independent variables and the remainder is explained by variables outside the model. F test results show that the independent variables together affect the productivity of soybeans. The result of t-test shows that Seed, manure, Gandasil fertilizer, GAP adoption rate significantly positive and NPK fertilizer significantly negatively affect soybean productivity.